THE PROBLEMS OF COMPLIANCE WITH THE LEGAL REGIME OF AGRICULTURAL LANDS WHEN PLACING LINEAR FACILITIES ON THEM - IGNATYEVA Inna Anatolyevna (Правовое государство: теория и практика)
The article raises the problem of using agricultural lands without providing land parcels and establishing a servitude or a public servitude. Judicial practice has formulated a position according to which linear facilities which meet the established characteristics may be placed on agricultural land on the specified basis. This does not correspond to the content of the law on land, which provides for the establishment of a public servitude in this case. The analysis of land law in this aspect is intended to show the features of the legal regime of agricultural lands, which can be ensured only by more precise legal constructions than «use of land and land parcels without provision». Purpose: to study land law regulation and legal acts in order to resolve the issue of correct realisation of legal institutions of public servitude and use without provision on agricultural lands. Methods: historical, systemic, analysis and synthesis, modelling and comparison. Results: the article concludes that it is unreasonable to place linear facilities on agricultural lands on legal grounds other than a public servitude. Such a rule is established in the legislation as an imperative rule, it cannot be interpreted variably. The legal regime of agricultural lands cannot be fully ensured in the use of lands and land parcels without providing and establishing a servitude, a public servitude due to the weak legal development of this institution.